2012
DOI: 10.1007/s10570-012-9675-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear modeling of equilibrium sorption of selected anionic adsorbates from aqueous solutions on cellulosic substrates. Part 1: model development

Abstract: A new nonlinear isothermal sorption model, incorporating Donnan equilibrium and electrical neutrality in the classical sorption model of direct dyes onto cellulosic substrates, as model adsorbates, is proposed. The nonlinear isothermal model was used to simulate equilibrium sorption of adsorbates containing ionic charges (z) of -2 to -4 on cellulose adsorbents at various temperature (T) and sodium chloride concentrations ([NaCl]). A detailed analysis of simulation results demonstrates that results based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Prior to fitting the nonlinear sorption model to the experimental data, all data points were tested to ensure the associated deviations of [Na ? ] S relative to Na þ ½ s were less than 5.0% as described elsewhere (Xu and Shamey 2012). The nonlinear sorption model was fitted to the experimental data by nonlinear leastsquares curve fitting.…”
Section: Model Fitmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to fitting the nonlinear sorption model to the experimental data, all data points were tested to ensure the associated deviations of [Na ? ] S relative to Na þ ½ s were less than 5.0% as described elsewhere (Xu and Shamey 2012). The nonlinear sorption model was fitted to the experimental data by nonlinear leastsquares curve fitting.…”
Section: Model Fitmentioning
confidence: 99%
“…7. In a previous study (Xu and Shamey 2012) it was shown that when relative deviation (RD) for [Na ? ] S in comparison to Na þ ½ s (Eq.…”
Section: Introductionmentioning
confidence: 99%